2021
DOI: 10.1002/ecs2.3618
|View full text |Cite
|
Sign up to set email alerts
|

Role of carryover effects in conservation of wild Pacific salmon migrating regulated rivers

Abstract: Determining which factors are most effective for mitigative strategies in conservation management can be difficult for species with complex life cycles. Salmon (Oncorhynchus spp.) migrating through a hydroelectric power system experience conditions that can affect their survival directly within a life stage and indirectly in subsequent life stages through carryover effects. We quantified the association of covariates with survival across life stages of Chinook salmon (O. tshawytscha): juveniles migrating downs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 97 publications
(207 reference statements)
0
7
1
Order By: Relevance
“…Surprisingly, the models suggest that hypoxia persisting greater than a week would be largely independent of temperature and this insensitivity may account for the low variability in T crit with CW type. Additionally, the CW framework arises in physiological and ecological studies (Mueller et al, 2015; Uchida, Uesaka, Yamamoto, Takeda, & Irie, 2018) and is implicit in studies that consider cross life‐stage effects (Del Rio et al, 2021; Gosselin et al, 2021; Stoks & Córdoba‐Aguilar, 2012). We suggest that further studies in a CW framework will provide new insights into embryogenesis and population regulation in a warming climate.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the models suggest that hypoxia persisting greater than a week would be largely independent of temperature and this insensitivity may account for the low variability in T crit with CW type. Additionally, the CW framework arises in physiological and ecological studies (Mueller et al, 2015; Uchida, Uesaka, Yamamoto, Takeda, & Irie, 2018) and is implicit in studies that consider cross life‐stage effects (Del Rio et al, 2021; Gosselin et al, 2021; Stoks & Córdoba‐Aguilar, 2012). We suggest that further studies in a CW framework will provide new insights into embryogenesis and population regulation in a warming climate.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that water temperature is a major factor in Chinook dynamics for both instantaneous interactions, as it influences migrating adult Chinook within a season and over multiple years. Within a year, water temperature can lead to higher disease, parasites, higher predation rates, and poorer ability to evade predators, and across years it may influence salmon over different life stages due to carryover effects [ 18 ].…”
Section: Results: 35-year Study (1984-2018)mentioning
confidence: 99%
“…For example, considering nonlinear environmental drivers has been found to improve forecast accuracy in fisheries models [ 16 ] and the extent to which a variable is predictive can depend on nonlinear thresholds [ 13 ]. It has also been found that there are multiple relevant indicators of salmon returns [ 17 ], carryover effects within salmon lifecyles in which conditions experienced at one life stage affect a subsequent stage [ 18 ] and marine survival [ 19 ], but no single indicator or subset of indicators is highly explanatory. Moreover, it has been found that the relationships between indicator variables themselves can be non-stationary [ 20 , 21 ], which has implications for predictive skills of models based on certain input combinations, and indicates the difficulty in distinguishing causal drivers from temporary correlations.…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest that estuarine growth can be an important “carryover” effect of estuary rearing (Gosselin et al. 2021) that relates to subsequent ocean survival. Together, these findings reinforce the importance of understanding the link between wetland restoration, chironomid production and export from wetland areas, and consumption of chironomids by migrating salmon smolts.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have demonstrated that the ocean survival of Columbia River steelhead and Chinook Salmon is positively related to juvenile length or growth rates at ocean entry (Claiborne et al 2011;Wilson et al 2021;Gosselin et al 2022;Norrie et al 2022). These studies suggest that estuarine growth can be an important "carryover" effect of estuary rearing (Gosselin et al 2021) that relates to subsequent ocean survival. Together, these findings reinforce the importance of understanding the link between wetland restoration, chironomid production and export from wetland areas, and consumption of chironomids by migrating salmon smolts.…”
Section: Growth Of Salmonmentioning
confidence: 94%